I - Q Cycles - Patrick Francois; Huw Lloyd-Ellis (Queen's University, Department of Economics, 2005)
We develop a model of "intrinsic" business cycles, driven by the decentralized behaviour of entrepreneurs and firms making continuous, divisible improvements in their productivity. We show how equilibrium cycles, associated with strategic delays in implementation and endogenous innovation, arise even in the presence of reversible investment. We derive the implications for the cyclical evolution of both tangible (physical) and intangible (knowledge) capital. In particular, our framework is consistent with key aspects of the somewhat puzzling relationship between fixed capital formation and the stockmarket at business cycle frequencies.
Keywords: E0; E3; O3; O4; 330; Tobinś Q; fixed capital formation; intangible investment; cycles and growth